Evaluate The Effect of Pretreatments and Drying Techniques on the Sweet Potato Slices - Ayman, S. Dyab; Ginat, M. El-Sherif; Rehab H. Gab-Allah (Food Technology Research Journal)
As the quality of dried products may vary greatly with different production procedures, the optimal procedures must be applied to produce dried products that meet consumer desires. Thus, the purpose of this study was to evaluate how different drying methods (ventilation oven, microwave, and combined microwave + ventilation oven) and pretreatments (blanching and 1% citric acid) affected the proximate composition, color, and sensory properties of sweet potato slices. Non-treated samples were used as control samples. The treatment contents of moisture, ash, total sugars, and ascorbic acid were measured both before and after drying. In comparison to blanched and control samples, sweet potato samples treated with a citric acid solution and microwave dried have the lowest decrease value across all drying methods. The obtained results suggested that ventilation oven adversely influenced the phenolic and flavonoid compounds of dried sweet potatoes. Among the methods used, the combined method and microwave had the greatest effect on phenolic compounds. The carotenoids and B-carotene values in dried treatments by the microwave drying method were higher than combined and ventilation oven methods, respectively. The data indicated that all treatments dried by the microwave method recorded a low change in the color change index (ΔE) value, particularly all samples treated with citric acid 1%. In fact, all of the samples treated with 1% citric acid demonstrated an acceptance index of up to 77.92%. Therefore, it was confirmed that the treatments using citric acid 1% and microwave drying were most suitable for sweet potato slices.